KESANTUNAN BERBAHASA DALAM INTERAKSI PENGGUNA TAXI PEDESAAN TANJUNG SELOKA - Faisal Batennie (STKIP Paris Barantai, 2014)
Ethnic diversity will bear the diversity of languages. The problems that arise when discussing the interaction of language diversity Seloka Tg society in the context of rural transport because of the many people who helped the role of various ethnic, professional and educational background which influences the way said language in accordance with the principles of politeness berbahasa.Oleh therefore, necessary for an evidence- evidence of the results of analysis work. Based on the above, there are many linguistic phenomenon that deserves to be studied. The phenomenon will be seen from the perspective of pragmatic in her study of the implementation and violations of politeness. Based on the results of research are: (a) the use of the principle of politeness on the activity of speech passenger, driver, helper, and touts on taxis rural transport Tanjung Seloka, (b) any irregularities politeness principle on the activity of speech passenger, driver, helper, and brokers in Tanjung Seloka taxi rural transportation. (C) the diversity of languages used in the speech of the passengers, the driver, helper and taxi touts at Tanjung Seloka rural transportation.Â Keywords: Politeness Speak, intraksi Taxi Rural Users